Situation Report: Poland, 13 March 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Rescheduling the Polish Debt Confusing Soviet-Polish Credit Arrangements Fifth Session of the Sejm: 11-12 February 1981 Rakowski Profile Sejm Passes 1981 Plan and Budget with Reservations Joint Commission Acknowledges Progress in Church-State Relations Lodz Settlement Puts an End to Students' Strikes Another Antialcohol Campaign Launched